Editors' Choice—Methanol Electrooxidation with Platinum Decorated Hematene Nanosheet. Issue 4 (23rd February 2019) - Zhang, Zishuai; Ye, Minnan; Harvey, Edward J.; Merle, Geraldine
Abstract : Developing a durable electrocatalyst with a high methanol oxidation reaction activity is highly important for anode design in direct methanol fuel cells. To that end, Pt-hematene sheets have been successfully synthesized by ultrasonic exfoliation followed by a double pulse deposition strategy to adjust the Pt loading. The morphology, structure, and composition of this new class of Pt decorated metal oxide nanosheet have been characterized by transmission electron microscopy, scanning electron microscopy and X-ray photoelectron spectroscopy. Electrocatalytic characteristics have been systematically investigated by cyclic voltammetry and compared with commercial Pt/C catalyst. The novel Pt-hematene sheets exhibit a good mass activity with a low peak potential but most of all show an enhanced tolerance to the intermediates of methanol oxidation.